Coupling of Epsilon-Near-Zero Mode to Gap Plasmon Mode for Flat-Top Wideband Perfect Light Absorption - Hendrickson, Joshua R; Vangala, Shivashankar; Dass, Chandriker; Gibson, Ricky; Goldsmith, John; Leedy, Kevin; Walker, Dennis E; Cleary, Justin W; Kim, Wonkyu; Guo, Junpeng (ACS photonics, 2018)
Epsilon-near-zero (ENZ) materials, when probed at or near wavelengths corresponding to their zero permittivity crossing points, have unique and interesting properties that can be exploited for enhancing nanoscale light–matter interactions. Here, we experimentally show that over an order of magnitude increase in the absorption band of a periodically patterned metal–dielectric–metal structure can be obtained by integrating an indium tin oxide (ITO) subwavelength nanolayer into the insulating dielectric gap region. Through incorporation of a 12 nm thick ITO layer between the patterned gold nanodisks and the SiO2 dielectric layer, a 240 nm wide, flat-top perfect (>98%) absorption centered at 1550 nm wavelength is enabled. The demonstrated wideband, perfect absorption resonance is shown to be due to coupling between the gap plasmon mode of the metasurface and the ENZ mode in the nanoscale ITO film.